High entropy alloy strengthening modelling. (1st September 2022) - Zang, Chengwei; Rivera-Díaz-del-Castillo, Pedro E J
Abstract: High entropy alloys (HEAs) have recently drawn attention due to their excellent mechanical properties across wide temperature ranges. This is attributed to phase stability and a wide variety of strengthening mechanisms in operation. Solid solution, precipitation, dislocation, grain-boundary, twin-boundary and phase-transformation strengthening have been reported to play an important role in controlling their mechanical properties. With a focus on yield strength, this paper reviews the different hardening mechanisms reported in the literature. Mathematical formulations and key constant for describing each mechanism are presented and discussed. A strengthening mechanism modelling strategy for HEA design is outlined.